Reviewing Fire, Climate, Deer, and Foundation Species as Drivers of Historically Open Oak and Pine Forests and Transition to Closed Forests - Hanberry, Brice B.; Abrams, Marc D.; Arthur, Mary A.; Varner, J. Morgan (Frontiers in Forests and Global Change, 2020)
Historically open oak and pine savannas and woodlands have transitioned to closed forests comprised of increased numbers of tree species throughout the eastern United States. We reviewed evidence for and against a suite of previously postulated drivers of forest transition focused on 1) change in fire regimes, 2) increased precipitation, 3) increased white-tailed deer densities, and 4) loss of American chestnut. We found that fire and fire exclusion provide a parsimonious mechanism for historical dominance by open forests of fire-tolerant oak and/or pine species and subsequent transition to closed forests with fire-sensitive tree species that fill the vertical profile. Based on statistical tests, increased precipitation during the past century was within historical ranges and thus fails to provide an explanation for forest change; additionally, precipitation variability is incongruent with tree traits (i.e. both drought-tolerant and drought-intolerant species have increased and decreased) and patterns of tree establishment. Similarly, current deer densities fail to provide a statistical relationship to explain tree densities at regional scales, species trends are unrelated to deer browse preferences, and both historically open forests and contemporary closed forests contained high deer densities. Functional extinction of the American chestnut had localized impacts but was not abundant compared to oak or widespread enough in distribution to match forest transitions throughout the eastern United States. Although Euro-American settlement affected many processes, not all changes were consistent enough to cause transitions in forest composition and structure that generally trailed westward expansion by Euro-American settlers. Evidence about these drivers continues to mount and we recognize the need for further research and continual re-evaluation of drivers of historical forests and forest change due to importance for understanding and management of these ecosystems.